TEACHING STUDENTS OF INFORMATION TECHNOLOGY SPECIALTIES ENGLISH WRITING - Olena Lazebna; Nataliia Dychka; Viktoriia Kotvytska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The paper deals with the problem of professional competence formation in ESP writing, which is especially important with the introduction of the new government standards for higher education. In this paper, the vital factors of acquiring knowledge, skills and abilities in English writing for students of IT specialties are studied. The importance of teaching students writing technical documentation − Software Requirements Specification − in English is emphasised taking into account the requirements of their educational qualification characteristics and programs. The difficulties which IT specialists have while writing professional texts in English are described. They are related to a technique of writing - spelling, punctuation skills; the language form - genre of the text, lexis and grammar; the content - compositional skills; the organisation of teaching - cooperation and correction of mistakes. The effectiveness of teaching ESP writing can be achieved through the combination of the classroom and the self-study work.